The relationship between exposure to phthalate metabolites and adult-onset hypogonadism - Liu, Zheng-Huan; Yang, Lu-Chen; Song, Pan; Chen, Jun-Hao; Peng, Zhu-Feng; Dong, Qiang (Frontiers in Endocrinology, 2022)
Objective. Adult-onset hypogonadism (AOH) is a common disease for males >40 years old and is closely associated with age-related comorbidities. Phthalates are compounds widely used in a number of products with endocrine-disrupting effects. However, little is known about the association between exposure to phthalates and the risk of AOH. Thus, we conducted this study to explore the potential association using the 2013-2016 National Health and Nutrition Examination Survey (NHANES) data. Method. Data on AOH and urinary phthalate metabolites were collected, and univariable and multivariable logistic regression analyses were adapted to evaluate the association. The concentrations of each metabolite were calculated and grouped according to their quartiles for the final analysis. Result. Finally, we found that the odds ratio (OR) increased with increased concentrations of di-(2-ethylhexyl) phthalate (DEHP) metabolites, including mono(2-ethyl-5-carboxypentyl) phthalate (MECPP), mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) and mono(2-ethyl-5-oxohexyl) phthalate (MEOHP). Simultaneously, a significant dose-dependent effect was also observed. The OR for the fourth quartile was highest among all three groups. Specifically, the ORs for the third quartile and fourth quartile were 1.774 and 1.858, respectively, in the MECPP group. For the MEHHP group, the OR increased from 1.580 for the second quartile to 1.814 for the fourth quartile. Similarly, the OR for the higher three quartiles varied from 1.424 to 1.715 in the MEOHP group. Conclusion. This study first revealed that there was a positive association between exposure to DEHP metabolites and the risk of AOH. These findings add limited evidence to study this topic, while further studies are needed to explain the potential molecular mechanisms.